Wheelchair Seating Assessment and Intervention: A Comparison between Telerehabilitation and Face-to-Face Service - Ingrid G Barlow; Lili Liu; Angela Sekulic (International Journal of Telerehabilitation)
This study compared outcomes of wheelchair seating and positioning interventions provided by telerehabilitation (n=10) and face-to-face (n=20; 10 in each of two comparison groups, one urban and one rural). Comparison clients were matched to the telerehabilitation clients in age, diagnosis, and type of seating components received. Clients and referring therapists rated their satisfaction and identified if seating intervention goals were met. Clients recorded travel expenses incurred or saved, and all therapists recorded time spent providing service. Wait times and completion times were tracked. Clients seen by telerehabilitation had similar satisfaction ratings and were as likely to have their goals met as clients seen face-to-face; telerehabilitation clients saved travel costs. Rural referring therapists who used telerehabilitation spent more time in preparation and follow-up than the other groups. Clients assessed by telerehabilitation had shorter wait times for assessment than rural face-to-face clients, but their interventions took as long to complete. Keywords: Telerehabilitation, Telehealth, Videoconferencing, Wheelchair Seating, Outcomes, Rehabilitation